Matches and mismatches between university teachers’ and students’ perceptions of E-learning: A qualitative study in China - Yan Liu (Heliyon, 2023)
Development in educational technology affected teaching at higher education institutes to a great extent. As a result, schools and universities have welcomed Electronic Learning (e-learning), most notably during the pandemic when educational institutes were closed. Different quantitative and qualitative researchers have mainly studied the quality of e-learning and its negative and positive consequences for societies, teachers, and students. However, matches and mismatches between university teachers' and students' perceptions of e-learning problems and advantages have not been well documented. Through a phenomenology study, this study delved into lived experiences of 25 teachers and 23 undergraduate students who were selected through theoretical sampling at Quzhou University in China. The data were collected through semi-structured interviews with the informants. The thematic analysis of the interviews revealed some matches and some mismatches between the teachers’ and students' perceptions of e-learning problems and advantages. Teachers, students, and other stakeholders can use findings to reduce the negative consequences and enhance the quality of e-learning.